Hodgkin lymphoma a comprehensive update on diagnostics and clinics - Engert, Andreas; Horning, Sandra J. (Hematologic malignancies., 2011)
This book provides a well-illustrated, comprehensive, and up-to-date account of Hodgkin lymphoma. Epidemiology, pathogenesis, and the role of the microenvironment are examined in detail. The initial clinical evaluation and use of staging systems are fully discussed, and prognostic factors are carefully considered. The various treatment options for first-line and relapsed Hodgkin lymphoma are presented, including the newly available treatments for recurrent disease and the management required in special clinical circumstances. Given the very high cure rates and the young age of many patients, there is an increasing need to develop better individually tailored treatment strategies that will help to avoid both early and late side-effects of treatment. Such strategies receive due attention, and clear guidance is provided on the handling of Hodgkin survivors. This book will be of great value to hematologists, oncologists, and all others with an interest in Hodgkin lymphoma.